1972
DOI: 10.1029/jb077i032p06435
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow and surface radioactivity at two sites in South Greenland

Abstract: Heat flow and surface radioactivity were determined at two sites in the Precambrian shield of south Greenland. At Ivigtut heat flow q from two holes in Ketilidian (•1700-1500 m.y.) gneisses averaged 1.0 ñ 0.1 HFU (•zcal cm -• sec-•), and the radiogenic heat production Ao averaged 5.5 ñ 1.5 HGU (10 -•8 cal cm -3 sec-•). These data are consistent with other pairs of q and Ao values from the Canadian and Australian shields. In four holes near the northwestern edge of the Ilimaussaq alkali intrusion of Gardar (•10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 20 publications
3
31
1
Order By: Relevance
“…The radioactive heat production of the crust is modeled as showing exponential decrease with depth with a scale depth of 8 km which is a typical value for Precambrian continental lithosphere (Artemieva & Mooney, ). The values for thermal conductivity and heat production were initially based on observations (Sandiford & McLaren, ) and were further optimized by comparing our model outputs with local heat flux estimates inferred from borehole temperature profiles in this study and by previous authors (Andersen & North Greenland Ice Core Project members, ; Buchardt & Dahl‐Jensen, ; Dahl‐Jensen et al, , ; Fahnestock et al, ; Greve, ; Hansen & Langway, ; Petrunin et al, ; Sass et al, ; Weertman, ). The majority of local values were determined from the deep boreholes: GRIP, NGRIP, Camp Century, NEEM, and DYE‐3, where there are ice temperature profiles available.…”
Section: Methodsmentioning
confidence: 99%
“…The radioactive heat production of the crust is modeled as showing exponential decrease with depth with a scale depth of 8 km which is a typical value for Precambrian continental lithosphere (Artemieva & Mooney, ). The values for thermal conductivity and heat production were initially based on observations (Sandiford & McLaren, ) and were further optimized by comparing our model outputs with local heat flux estimates inferred from borehole temperature profiles in this study and by previous authors (Andersen & North Greenland Ice Core Project members, ; Buchardt & Dahl‐Jensen, ; Dahl‐Jensen et al, , ; Fahnestock et al, ; Greve, ; Hansen & Langway, ; Petrunin et al, ; Sass et al, ; Weertman, ). The majority of local values were determined from the deep boreholes: GRIP, NGRIP, Camp Century, NEEM, and DYE‐3, where there are ice temperature profiles available.…”
Section: Methodsmentioning
confidence: 99%
“…Indirect evidence of the character of the substratum in Ilimaussaq comes from geophysical data. Heat-flow measurements (Sass et al 1972) have shown that the agpaitic rocks constitute a surface layer with a thickness not much greater than that of the exposed agpaitic rocks. A large positive gravity anomaly is centred in the Ilimaussaq area (Blundell 1978;Forsberg & Rasmussen 1978) where there is also a large magnetic anomaly (L. Thorning, personal communication).…”
Section: Structure Of the Ilimaussaq Intrusionmentioning
confidence: 99%
“…-72-tion, all we can state with assurance is that the high radiogenic heat production of the Stripa quartz monzonite, together with the regionally "normal" heat flow measured in the pluton, suggests that the relatively radioactive quartz monzonitic body is small; this body appears to have little if any effect on the regional heat flow. Similar circumstances were observed at the peralkalic plutons of Ilimaussaq, Greenland (Sass et al, 1972) and Pocos de Caldas, Brazil (Vitorello et al, 1980), where high radiogenic heat production is not matched by higher-than-normal heat flow.…”
Section: Variation With Depthmentioning
confidence: 50%